The Second Victim: Can We Identify Those Most At Risk? [18G]. Issue 1 (May 2017) - Benham, Joshua; Liebermann, Joan; Gaba, Nancy; Amdur, Richard; Margulies, Samantha; Keller, Jennifer
Abstract : INTRODUCTION: Maternal and perinatal deaths impact those providing care to these patients ("second victims"). Limited research exists to determine who is likely to experience post traumatic stress disorder (PTSD), depression or anxiety after a maternal or perinatal death. METHODS: A survey was distributed by email to all Women's Services staff (including Neonatal ICU) at an urban university hospital. The survey asked about experiences with perinatal and maternal death and included questions from validated screening tools for PTSD (PC-PTSD) and depression (PQH4). RESULTS: There were 105 responses to the survey. 43 of the responders were physicians. The remaining responders were midwives, nurses, techs and administrative staff. A multivariate model was used to test the independent association of predictors with outcomes and was used to develop prediction models. Four variables were predictive of a "negative outcome" (defined as experiencing anxiety, depression, post-traumatic stress symptoms, or work problems). These included: (1) a non-physician role, (2) substance use, (3) career change consideration, and (4) seeking mental health treatment after an event. With each additional risk factor, the negative outcome score increased significantly. Age, sex, religious beliefs, marital or parental status, and level of clinical involvement with patient/baby were not significantly correlated with negative outcomes. CONCLUSION: When providing support for team members involved in a maternal or perinatal death, individuals at risk for PTSD, anxiety, depression and work related problems should be identified and supported. Future studies will focus on the best way to assist those impacted by these events.